2017
DOI: 10.1021/acs.iecr.7b03322
|View full text |Cite
|
Sign up to set email alerts
|

Supernucleating Role of Poly(ω-pentadecalactone) during the Crystallization of Poly(ε-caprolactone) Composites

Abstract: Inspired by the epitaxial crystallization theory and isomorphism phenomenon, poly(ω-pentadecalactone) (PPDL) and the random copolyesters of ω-pentadecalactone and ε-caprolactone Poly(PDL-co-CL)s have been synthesized and tested as polymeric nucleating agents for commercial poly(ε-caprolactone) (PCL). Crystallization behavior and spherulite structure of the neat PCL and nucleated PCL specimens have been investigated by differential scanning calorimetry (DSC), polarized optical microscopy (POM), and atomic force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…[ 36 ] Also, Ye and Yao reported that CL/PDL copolymers exhibit a super nucleation role in PCL matrices. [ 37 ] Wilson et al. included CL units within PPDL chains to increase its hydrolytic degradation rate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 36 ] Also, Ye and Yao reported that CL/PDL copolymers exhibit a super nucleation role in PCL matrices. [ 37 ] Wilson et al. included CL units within PPDL chains to increase its hydrolytic degradation rate.…”
Section: Methodsmentioning
confidence: 99%
“…[36] Also, Ye and Yao reported that CL/PDL copolymers exhibit a super nucleation role in PCL matrices. [37] Wilson et al included CL units within PPDL chains to increase its hydrolytic degradation rate. [23] These illustrative examples highlight the need for CL/PDL copolymerizations that can be carried out at larger scale, in-bulk, without the need for strict exclusion of O 2 (g) as well as water and provide high molecular copolymers.…”
mentioning
confidence: 99%
“…In recent years, as the growing environmental awareness and shortage of natural resource, biodegradable and biobased polymer materials have received significant interest in numerous areas as a substitute of conventional petroleum‐based manufacture . Such as poly(lactic acid) (PLA), polycaprolactone (PCL), and their blends or composites, have been deeply explored and applied for several decades . Poly(glycolic acid) (PGA), as a kind of aliphatic polyester with a similar macromolecular structure to PLA, has been mainly used in biomedical engineering such as suture material due to its excellent mechanical properties, biocompatibility, and predictable biodegradation via hydrolysis into natural metabolic waste products .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Such as poly(lactic acid) (PLA), polycaprolactone (PCL), and their blends or composites, have been deeply explored and applied for several decades. [4][5][6][7] Poly(glycolic acid) (PGA), as a kind of aliphatic polyester with a similar macromolecular structure to PLA, has been mainly used in biomedical engineering such as suture material due to its excellent mechanical properties, biocompatibility, and predictable biodegradation via hydrolysis into natural metabolic waste products. [8,9] PGA also has some drawbacks, such as high sorption of water, over quick degradation rate in the natural environment, and higher price.…”
Section: Introductionmentioning
confidence: 99%
“…tensile performance of melt-drawn PPDL fibres reinforced in situ with a vanillic acid-based thermotropic liquid crystalline polyester (LCP) was enhanced with increasing LCP orientation and concentration (up to 30 wt.%) via interfacial crystallization, which delocalises stress between the PPDL/LCP interface (Figure 12) [235]. Furthermore, PPDL and statistical PPDL-co-PCL copolyesters were demonstrated to be effective nucleating agents for commercial PCL, increasing the number of spherulites, accelerating the nonisothermal rate of crystallization, increasing the Tc, and enhancing the tensile strength of the material by 12.4% while maintaining the same elongation at break [236]. Blending PPDL (up to 30 wt.%) into poly(L-LA) (PLLA) films increased the Young`s moduli of these materials from 670 MPa to 1010 MPa,[57] and PPDL-b-PLLA copolymers were shown to be efficient compatilising agents in blending PLLA with high carbon content polymers such as poly(ω-hydroxytetradecanoate), HDPE, and LDPE [99,135].…”
mentioning
confidence: 98%